2019
DOI: 10.3390/nu11102474
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Premenopausal Women Is Associated with the Dietary Intake of α-Tocopherol: A Cross-Sectional Study

Abstract: This study aimed to investigate the relationship between the consumption of various nutrients and bone mineral density (BMD) in middle-aged women. This cross-sectional survey was conducted based on the clinical records of 157 women aged 38–76. Their lumbar spine BMD was measured with dual-energy X-ray absorptiometry and dietary habits were assessed with the brief-type self-administered diet history questionnaire. Participants were divided into premenopausal (n = 46) and postmenopausal (n = 111) groups and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Zhang et al identified a negative association between serum α-tocopherol concentration and bone mineral density in an elderly US population [ 200 ], and Ilesanmi-Oyelere et al reported that a diet rich in vitamin E and fats was associated with lower bone mineral density in postmenopausal women [ 201 ]. On the other hand, Odai et al’s cross-sectional study showed that dietary intake of vitamin E was associated with higher bone mineral density in premenopausal women but had no effect in postmenopausal women [ 202 ]. Yang et al found no effect of vitamin E on bone turnover markers or bone mineral density in peri- or postmenopausal women in the UK [ 203 ].…”
Section: Recent Pre-clinical Studiesmentioning
confidence: 99%
“…Zhang et al identified a negative association between serum α-tocopherol concentration and bone mineral density in an elderly US population [ 200 ], and Ilesanmi-Oyelere et al reported that a diet rich in vitamin E and fats was associated with lower bone mineral density in postmenopausal women [ 201 ]. On the other hand, Odai et al’s cross-sectional study showed that dietary intake of vitamin E was associated with higher bone mineral density in premenopausal women but had no effect in postmenopausal women [ 202 ]. Yang et al found no effect of vitamin E on bone turnover markers or bone mineral density in peri- or postmenopausal women in the UK [ 203 ].…”
Section: Recent Pre-clinical Studiesmentioning
confidence: 99%
“…Limited research exists, mainly in older adults, which suggests that vitamin E, a lipid-soluble, anti-oxidant vitamin, may also be protective with respect to muscle mass and frailty [ 21 , 22 , 23 , 24 , 25 , 26 ], as skeletal muscle is the organ with the highest consumption of oxygen in the body. Positive associations of vitamin E intake with bone mineral density (BMD) and fracture risk have also been reported in both men and women [ 27 , 28 , 29 , 30 ]. The major forms of vitamin E in food are the α- and γ-tocopherols, and thus these are found in greater abundance than other tocopherols and tocotrienols in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Li et al [ 37 ] reported that the intake of fruits and vegetables was significantly associated with whole-body BMC, but not with the BMC and BMD of specific sites in premenopausal women. In premenopausal women, vitamin C intake was positively associated with femur BMD [ 42 ], vitamin E intake was positively correlated with lumbar BMD [ 9 ], and carotenoid intake was positively linked to the BMD of the total hip [ 6 ]. These findings suggest that the effect of a single antioxidant on BMD could be site-specific in premenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial association between antioxidant intake, bone mass, and the risk of osteoporosis has been studied in many countries, including the Republic of Korea [ 6 , 8 , 12 , 14 , 15 ], China [ 10 , 13 ], and Japan [ 9 ]. However, these studies primarily focused on the effects of single antioxidant intake, which might not fully explain the effects of all antioxidants in the diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation